Persistence of traditional and emergence of new structural drivers and factors for the HIV epidemic in rural Uganda; A qualitative study - Bajunirwe, Francis; Akakimpa, Denis; Tumwebaze, Flora P.; Abongomera, George; Mugyenyi, Peter N.; Kityo, Cissy M. (Plos one, 2019)
In Uganda, the HIV epidemic is now mature and generalized. Recently, there have been reports of resurgence in the incidence of HIV after several years of successful control. The causes for this resurgence are not clear but suspected to be driven by structural factors that influence large groups of people rather than individuals. The aim of this study was to describe the structural drivers of the HIV epidemic in high prevalence regions and inform the next generation of interventions.We conducted a total of 35 focus group discussions in 11 districts in Uganda. Due to their high HIV prevalence, the districts had been selected to implement a donor supported program to scale up HIV prevention, care and treatment. Focus groups consisted of men and women including opinion leaders, civil servants including teachers, police officers, religious, political leaders, shop keepers, local residents and other ordinary persons from all walks of life. The qualitative data were transcribed and analyzed manually. Texts were coded using a coding scheme which was prepared ahead of time but emerging themes and codes were also allowed.Our data indicated there is persistence of several structural drivers and factors for HIV in rural Uganda. The structural drivers of HIV were divided into three categories: Gender issues, socio-cultural, and economic drivers. The specific drivers included several gender issues, stigma surrounding illness, traditional medical practices, urbanization, alcohol and substance abuse and poverty. New drivers arising from urbanization, easy access to mobile phone, internet and technological advancement have emerged. These drivers are intertwined within an existing culture, lifestyle and the mixture is influenced by modernization. The traditional structural drivers of HIV have persisted since the emergence of the HIV epidemic in Uganda and new ones have emerged. All these drivers may require combined structural interventions that are culturally and locally adapted in order to tackle the resurgence in incidence of HIV in Uganda.